Application of adaptive filter in fruit quality inspection based on its acoustic properties - RAO Xiu-qin; YING Yi-bin (浙江大学学报. 农业与生命科学版, 2003)
The fruit quality inspecting system consisted of a electromagnet, a striking ball wrapped in rubber, a sensor with 2 microphones at a distance of 0.06 m, a set of signal processing circuit, and a computer with a data acquisition board. The signal was amplified and filtered by a processing circuit, whose pass band is from 3 to 3000 Hz. The processed signal was sampled at a rate of 10kHz with the data acquisition board PCL-1800 (Advantech Co., Ltd.). An adaptive filter was designed to filter noise from the signal sampled during test which improved the effectives of the signal. The results showed that the correlation coefficient was elevated from 0.54943 to 0.94684 after filtering, and it was also found the energy of real signal and noise focused on 0-230 Hz and 90-350 Hz respectively.